The Influence of Lifestyle, Perceived Convenience, And Promotion on The Decision to Use Quick Response Code Indonesian Standard (QRIS) - Endyastuti Pravitasari; Annisa Fauziyah (Return : Study of Management, Economic and Bussines, 2023)
This study aims to determine the effect of lifestyle, perceived convenience, and promotion on the decision to use the Indonesian Standard Quick Response Code (QRIS). Indonesia has already developed a QR Code-based transaction system that can be used for digital payments and is known as QRIS (Quick Response Code Indonesian Standard). This research is a quantitative study with a total of 349 respondents QRIS users in Indonesia who are over 17 years old. Sampling used a convenience sampling of  nonprobability sampling technique by distributing questionnaires on social media. Data processing using SPSS software. This result shows that there are positive significan influence between lifestyle on the decision to use, positive influence between perceived convenience on  the decision to use, and  positive influence between promotions on  the decision to use. This research is hoped to be able to support the growth and acceptance of QRIS as an increasing popular digital payment tool in Indonesia.